2016
DOI: 10.1007/978-3-319-47313-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Motor Lateralization Provides a Foundation for Predicting and Treating Non-paretic Arm Motor Deficits in Stroke

Abstract: Brain lateralization is a ubiquitous feature of neural organization across the vertebrate spectrum. We have developed a model of motor lateralization that attributes different motor control processes to each cerebral hemisphere. This bilateral hemispheric model of motor control has successfully predicted hemisphere-specific motor control and motor learning deficits in the ipsilesional, or non-paretic, arm of patients with unilateral stroke. We now show across large number and range of stroke patients that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…‘Postural instability’ is significantly more frequent among patients with right-hemisphere lesions, while ‘apraxic responses’ predominate among those with left-hemisphere injury ( Spinazzola et al , 2003 ). Consistently, animal studies showed that changes in locomotor behaviour and correlated region-specific differences in turnover of neurotransmitters after somatosensory TBI were dependent on the side of brain injury ( Robinson, 1979 ; Pearlson and Robinson, 1981 ; Spinazzola et al , 2003 ; Perennou et al , 2008 ; Sainburg, 2014 ; Sainburg et al , 2016 ; Ocklenburg et al , 2017 ; Fernandes et al , 2018 ; Stancher et al , 2018 ). Right but not left somatosensory lesions produced behavioural hyperactivity and bilaterally decreased cerebral and locus ceruleus norepinephrine concentrations.…”
Section: Introductionmentioning
confidence: 68%
“…‘Postural instability’ is significantly more frequent among patients with right-hemisphere lesions, while ‘apraxic responses’ predominate among those with left-hemisphere injury ( Spinazzola et al , 2003 ). Consistently, animal studies showed that changes in locomotor behaviour and correlated region-specific differences in turnover of neurotransmitters after somatosensory TBI were dependent on the side of brain injury ( Robinson, 1979 ; Pearlson and Robinson, 1981 ; Spinazzola et al , 2003 ; Perennou et al , 2008 ; Sainburg, 2014 ; Sainburg et al , 2016 ; Ocklenburg et al , 2017 ; Fernandes et al , 2018 ; Stancher et al , 2018 ). Right but not left somatosensory lesions produced behavioural hyperactivity and bilaterally decreased cerebral and locus ceruleus norepinephrine concentrations.…”
Section: Introductionmentioning
confidence: 68%
“…Unfortunately, almost all these prior studies have ignored the impact of the hemisphere of brain damage on the relationship between clinical impairment measures and arm use patterns. This is despite growing evidence that damage to the left or right hemisphere produces distinct behavioral deficits (Mani et al, 2013;Schaefer, Haaland, & Sainburg, 2009;Schaefer, Mutha, Haaland, & Sainburg, 2012;Winstein & Pohl, 1995), and that these differential deficits hold significant implications for rehabilitation (Sainburg, & Duff, 2006;Sainburg, Maenza, Winstein, & Good, 2016). For example, a large body of work has shown that motor control (Haaland, Prestopnik, Knight & Lee, 2004;Mani et al, 2013;Schaefer et al, 2009;Winstein & Pohl, 1995), error correction (Schaefer et al, 2012) and learning (Garry, Kamel & Nordstrom, 2004;Mutha, Sainburg, & Haaland, 2011a,b) are all differentially affected in patients with left versus right hemisphere damage when they are tested on point-to-point reaching movements.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of interlimb transfer is of particular interest to rehabilitation specialists, as it has therapeutic implications for individuals with unilateral motor deficits, such as stroke or hemiparetic cerebral palsy. For example, there is a growing interest in training the lessimpaired limb to improve motor performance and functional deficits in the more-impaired limb of stroke survivors [3,4]. However, our understanding of practice strategies that could potentially enhance the transfer of motor skills from one limb to the other is limited, particularly for tasks with functional relevance, such as gait.…”
Section: Discussionmentioning
confidence: 99%
“…Interlimb transfer is the process in which training of one limb confers a benefit in performance to the opposite, untrained limb [1,2]. This ability of the neuromotor system to transfer the knowledge gained from training with one limb to the other limb is a key aspect of motor recovery in individuals with significant unilateral deficits, such as stroke or hemiparetic cerebral palsy [3,4]. Thus, understanding the processes that lead to stronger interlimb transfer may have therapeutic implications, as it can assist in the development of new treatment approaches.…”
Section: Introductionmentioning
confidence: 99%